Tes Takayama sebagai Sarana Identifikasi Sampel Darah Terpapar Media Dekomposisi Tanah: Takayama Test as a Means of Identification of Blood Samples Exposed to Soil Decomposition Media - Oktavia Sari; Eriko Prawestiningtyas (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
In criminal cases, blood spots are one of the markers of a crime. Spots left on an object, no matter how small, can be used as evidence, whether it comes from humans or not. Criminals often try to eliminate traces of their actions by hiding or disposing of bloodstained items in the hope of complicating the investigation process. This study refers to the use of the Takayama Test in determining the origin of blood spots. This test is one of the method to test whether the spots found are blood or not, and confirm th origin of the blood. Based on the number of cases in which the perpetrators disposed of evidence, this study aims to determine the extent to which the Takayama Test is used to identify blood spots on cloth with the influence of soil decomposition media. The study used a True Experimental design with randomization and a control group. Data analysis using descriptive analysis. The results obtained from observations for 30 days, the Takayama test showed positive results and could identify the presence of blood spots on the soil decomposition media. A positive result is indicated by the presence of hemochromogen crystals that form on blood spots that have been exposed to the soil. The formation of brownish black crystals was found in the spots exposed to the soil medium.